Affordances of digital platforms in sub‐Saharan Africa: An analytical review. Issue 4 (23rd January 2022) - Daramola, Olawande; Etim, Ernest
Abstract: The proliferation of digital platforms in sub‐Saharan Africa (SSA) has increased job opportunities for informal businesses. However, the technological affordance of digital platforms in SSA has received very little attention in literature review. This paper presents an analytical review of the technological affordances of digital platforms in SSA. We adopted a systematic literature review methodology that entailed gathering evidence from relevant literature and digital platforms in three countries in SSA (South Africa, Nigeria, and Kenya). Three research questions focusing on (i) critical issues of discussion on digital platforms in SSA and their distribution; (ii) understanding the technological affordances of digital platforms in SSA; and (iii) assessing the extent to which the technological affordances digital platforms can address the challenges of the informal sector in SSA drove the investigation. The study developed an affordances criteria framework, the first of its kind, to evaluate digital platforms affordances in SSA. Our findings revealed the key topics that have gained researchers' attention so far and digital platforms distribution in SSA. We also found that most digital platforms in SSA currently lack affordances that support multimodal interface and native language contents, limiting their accessibility to persons with minimal digital literacy. Most platforms also lack support for public/private partnerships. The lack of critical affordances that match the profile of the informal sector in SSA makes existing digital platforms incapable of addressing many critical challenges of the informal sector. These challenges include low literacy levels, minimal/lack of government support, lack of electricity or expensive power supply, expensive internet connectivity, and health and safety issues. However, existing digital platforms can reasonably address the absence of social protection, lack of formalization, and poor operational infrastructure. As a contribution, this paper offers a new perspective on the technological affordances of digital platforms in SSA. It also provides insight into the imperatives for designing inclusive and accessible digital platforms for the informal sector in SSA.